Невикористані можливості в розвитку Україні: екологічні та економічні втрати - Дмитрієва, Вікторія Анатоліївна; Dmytriieva, Viktoriia (Миколаївський національний аграрний університет, 2020)
Багатовікова діяльність людства, особливо останні десятиріччя швидкого технологічного прогресу, тісно пов’язані зі зростанням обсягів викидів в повітря та водні басейни, зі стійким накопиченням небезпечних продуктів діяльності, що охоплюють великі площі земель, які згодом стають непридатним для сільськогосподарського використання. В статті подано результати аналізу ефекту таких побічних проявів розвитку, як негативні тенденції акумуляції побутових відходів та нераціонального використання водних природних ресурсів, що не лише шкодять природному середовищу країни, а й призводять до недоотримання економічних вигод. Зокрема, зіставлено стан висвітлення проблеми подолання наслідків технологічного прогресу в міжнародних та вітчизняних відкритих джерелах; виявлено особливості представлення інформації щодо даної проблеми в Україні; за офіційними статистичними даними проаналізовано специфіку поводження з побутовими відходами; оцінено імовірні економічні втрати від нераціонального використання водних ресурсів та необлікованих, а отже, неконтрольованих витрат, при поводженні з відходами. Розглянуто регіональний аспект та простежено тенденції загалом по країні. В статті враховано період останнього десятиріччя, та в окремих випадках взято до уваги довгострокову динаміку числових показників описаної предметної області. Centuries human’s activity, especially last decades of rapid technological rise, is closely related to increasing emission volumes of harmful substances intoatmosphere and water basins, sustainable accumulation of dangerous by-products that occupied huge land areas that have already become unusable for agriculture. Lack of technologies and financial resources to clean up air, water and landfills is the biggest problem for majority countries. This problem causes threats for healthy vitality at least in a nearest future. Moreover, irrational use of resources leads to economic losses and income decline thatmeans decreasing of chances for quality economic development. International society improves not only practice in organizing statistical data, monitoring situation in environment pollution, but they also find out approaches to prevent accumulation of waste and greenhouse gases emission, study in which way implemented actions can be successful ecologically and economically. The problem solving in Ukraine has some peculiarities and among them are the set of indicators that describe level of environment pollution in our country, tolerance to waste accumulating and losses of nature resources. Since 1992 Ukraine had joined to United Nations Framework Convention on Climate Change and synchronized statistical data according to it demands. It is eager to investigate with official data what the special features in our country are in both ecological and economic problems and what the tendency in their solving is.Purpose. To analyze and reveal peculiarities of lateral results of economic development in Ukraine and to assess probable profits or losses to avoid or to deal with their impact.Results. Official government statistics presents annually different reports and results of environment pollution monitoring, but, unfortunately, it has some lack of detailed information about economic and ecological effect in recycling, emission decreasing and waste utilization (except accumulating on landfills or burning) by factories that produce or recycle it. Besides that, analysis of dynamics in waste management revealed that from 30% to 45% of gathered waste are not accounted and itis leaving unknown what is happening with it than. In use of water resources subjects of business activity are not thrifty. For instance, in 2018 nearly 17% of water was lost in transportation process that meant considerable cutback of gross domestic product in regions. Conclusion. Tolerance to uncontrolled waste accumulating, losses of any nature resources can damage both environment and economy in any country. Keeping of such tendency is dangerous for healthy life and activity of modern and future generations in Ukraine.
Unused Development Opportunities in Ukraine: Environmental and Economic Losses
Keywords: економічні витрати; economic expenditures; забруднення середовища; pollution of environment; тенденція поводження з відходами; tendency of waste management; динаміка; dynamics; необліковані відходи; uncounted costs; валовий регіональний продукт; gross domestic product